LIPID METABOLISM IN DIABETIC RATS AS AFFECTED BY CANOLA AND MUSTARD SEED SPROUTS - Hanaa Amer; Tahany Aly; K. Tobgy; M. Abdallah; N. El-Shahat (Arab Universities Journal of Agricultural Sciences, 2019)
Canola (Brassica juncea L.) and mustard (Sinapis alba L.) seed sprout effects on diabetic rats  have no available information and to clarify their effects, both sprouts were investigated in streptozotocin (STZ) induced diabetic and normal rats. Rats were fed on a semi-modified diet containing 10% of canola or mustard sprouted using tap or saline water for sprouting ad-libitum for 6 weeks. STZ showed increases in blood sugar, low density lipoprotein cholesterol (LDL-c), vary low density lipoprotein cholesterol (VLDL-c) and triglycerides (TG). The addition of canola and mustard with or without salinty at 10% to diabetic rats diet as semimodified diet resulted a significant decrease in blood glucose, TG and VLDL-c and data was more pronounced using mustard sprouted or saline water without changes in the HDL-c   parameter. These results showed that canola and mustard especially mustard sprouted in saline water had a hypoglycemic activity in diabetic rats and partly improved lipid metabolism in the experimental rats, with non-toxic to rats in doses given  over 6 weeks period in this study.